School Based Intervention sebagai Upaya Perbaikan Konsumsi Buah dan Sayur Siswa Sekolah Dasar - Damelya Patricksia Dampang; Lilik Kustiyah; Cesilia Meti Dwiriani (Media Kesehatan Masyarakat Indonesia, 2018)
School age children are susceptible to experiencing nutritional problems, one of which is due to environmentalfactors, especially the physical environment which provides broad, affordable food, higher energy densityand lack of consumption of fruits and vegetables. The efforts to improve the habit of eating fruits and vegetables inschool children is the existence of school based intervention. This study aim to analyze the effect of school basedintervention program to increase of fruit and vegetable consumption of elementary school students. The studytook place from February to May 2017 in Nganjuk, East Java. This study used experimental design with pre-postintervention with the number of subjects is 50 students (10-13 years) given three types of interventions is schoolgardening, cooking class, and giving of fruit and vegetables in school. The results showed that the presence ofthese three interventions can increased fruit consumption 130 g/day and vegetable 100 g/day and the availabilityof fruit and vegetables at home increased 81 g/week and 182 g/week. The results from recall SQ-FFQ 2x24 hoursshowed the average consumption of energy density decreased from 1420 kcal to 1241 kcal. Based on these results,school based intervention can be used as a strategy to increase fruit and vegetable consumption and availabilityfruit and vegetable at home